PENGARUH PENERAPAN GREEN ACCOUNTING DAN KINERJA LINGKUNGAN TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Prena, Gine Das (Jurnal Akun Nabelo: Jurnal Akuntansi Netral, Akuntabel, Objektif, 2021)
The purpose of this study is 1) to determine the effect of green accounting implementation toward financial performance of manufacturing companies in Indonesia Stock Exchange 2) to determine the effect of environmental performance toward financial performance of manufacturing companies in Indonesia Stock Exchange. In this study using two independent variables, green accounting implementation and environmental performance, with 1 dependent variable, financial performance. This research was conducted on manufacturing companies in Indonesia Stock Exchange in 2016-2018. Data collection techniques in this study used secondary data using annual report of companies and PROPER decision letter in 2016-2018. The sample in this study were 44 manufacturing companies in Indonesia Stock Exchange in 2016-2018. Data were analyzed using multiple linear regression analysis techniques, coefficient of determination, simultaneous significance test (F test), and partial test (t test) with the help of SPSS software for windows.Â The results of this study is 1) Green Accounting Implementation had a notÂ  significant effect on financial performance of manufacturing companies in Indonesia Stock Exchange 2) Environmental performance has a positive and significant effect on financial performance of manufacturing companies in Indonesia Stock Exchange.